Role Fulfillment Mediates the Association Between Daily Family Assistance and Cortisol Awakening Response in Adolescents. Issue 3 (10th January 2019) - Armstrong‐Carter, Emma; Ivory, Susannah; Lin, Lynda C.; Muscatell, Keely A.; Telzer, Eva H.
Abstract : Family assistance (helping the family) is associated with both positive and negative psychological and biological outcomes during adolescence. However, the association between family assistance and the hypothalamic–pituitary–adrenal (HPA) axis remains unstudied. Thus, we assess how helping the family relates to adolescents' diurnal cortisol, an index of HPA activity, and psychological outcomes. Three hundred and seventy ethnically diverse adolescents (ages 11–18) reported daily helping behaviors and psychological experiences for 14 days and provided four saliva samples per day for 4 days. Multilevel modeling revealed that cortisol awakening response was lower the day after adolescents helped their families more. This association was explained, in part, by perceived role fulfillment (feeling like a good son, daughter, and sibling). Results highlight a possible psychological and biological benefit of assisting the family during adolescence.